Hegel and the Future of Systematic Philosophy - Winfield, R. author. aut Link
XV, 210 p.
Keywords: Hegel and the Future of Systematic Philosophy critically rethinks and extends Hegel's project for systematic philosophy without foundations, engaging the most important contemporary debates concerning logic, epistemology, metaphysics, nature, mind, economic justice, political freedom, globalization, and literary theory.